Mathematical model of evaluation of rehabilitation efficiency increase with the help of personalized rehabilitation selection technology with the help of adapted virtual environment - A. V. Zakharov; S. S. Chaplygin; A. V. Kolsanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
The paper analyzes the possibility of using multi-sensory virtual reality to increase the effectiveness of rehabilitation measures based on the ideomotor representation of complex bilateral limb movements. Mathematical models were constructed in the form of statistical connectors of intercortical interactions undergoing changes against the background of peripheral sensomotor apparatus activation. The increased activity in the motor cortical zones of the proprioceptive system activation was demonstrated, which testifies to the increased efficiency of the ideomotor representation of movements. The obtained results can be used as a way to improve the stability and accuracy of neurocomputer interface classifiers based on the detection of complex bilateral movements.